Lichen planopilaris is characterized by immune privilege collapse of the hair follicle's epithelial stem cell niche. Issue 2 (10th September 2013) - Harries, Matthew J; Meyer, Katja; Chaudhry, Iskander; E Kloepper, Jennifer; Poblet, Enrique; Griffiths, Christopher EM; Paus, Ralf
Abstract Lichen planopilaris (LPP) is a chronic inflammatory disease of unknown pathogenesis that leads to permanent hair loss. Whilst destruction of epithelial hair follicle stem cells (eHFSCs) that reside in an immunologically protected niche of the HF epithelium, the bulge, is a likely key event in LPP pathogenesis, this remains to be demonstrated. We have tested the hypotheses that bulge immune privilege (IP) collapse and inflammation‐induced eHFSC death are key components in the pathogenesis of LPP. Biopsies of lesional and non‐lesional scalp skin from adult LPP patients (n = 42) were analysed by quantitative (immuno)histomorphometry, real‐time quantitative polymerase chain reaction (qRT–PCR), laser capture microdissection and microarray analysis, or skin organ culture. At both the protein and transcriptional level, lesional LPP HFs showed evidence for bulge IP collapse (ie increased expression of MHC class I and II, β2microglobulin; reduced TGFβ2 and CD200 expression). This was accompanied by a Th1‐biased cytotoxic T cell response (ie increased CD8+ GranzymeB+ T cells and CD123+ plasmacytoid dendritic cells, with increased CXCR3 expression) and increased expression of interferon‐inducible chemokines (CXCL9/10/11). Interestingly, lesional LPP eHFSCs showed both increased proliferation and apoptosis in situ. Microarray analysis revealed a loss of eHFSC signatures and increased expression of T cell activation/binding markers in active LPP, while bulge PPARγ transcription was unaltered compared to non‐lesional LPP HFs. In organ culture of non‐lesional LPP skin, interferon‐γ (IFNγ) induced bulge IP collapse. LPP is an excellent model disease for studying and preventing immune destruction of human epithelial stem cells in situ. These novel findings raise the possibility that LPP represents an autoimmune disease in whose pathogenesis IFNγ‐induced bulge IP collapse plays an important role. Therapeutically, bulge IP protection/restoration may help to better manage this highly treatment‐resistant cicatricial alopecia. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.